Design of durable concrete structure - Barthwal, Rahul (SCITUS Academics, 2016)
Concrete structures are designed so that they can satisfy requirements regarding safety, serviceability, durability and aesthetics throughout their design service life. The durability aspect is a natural extension of the classical resistance verification where deterioration effects are normally neglected. The reliability is assessed through the given performance that must be delivered within the design service life, the so-called performance-based design. This approach can be adopted for a performance based on service life design. In the recent years design is related to durability through the analysis of carbonation, resistance to chloride ingress, improved freezing and thawing resistance, etc. The review of literature and some recommendations are presented referring to the design of structures aiming to attain greater durability of concrete structures. The accent is put on the theory of reliability, failure probability and service life probability. The basics of this analysis are given through the principles of performances and service life, and deterministic and scholastic methods using the lifetime safety factor.